2017
DOI: 10.21474/ijar01/4051
|View full text |Cite
|
Sign up to set email alerts
|

THE EPIDEMIOLOGY AND FACTORS ASSOCIATED WITHNOCTURNAL ENURESIS AMONG SCHOOL & PRESCHOOL CHILDREN IN HAIL CITY, SAUDI ARABIA: A CROSS-SECTIONAL STUDY.

Abstract: Background: Enuresis, which is frequently diagnosed amongst schoolchildren, is an important psychosocial problem for both parents and children. Objectives: In the present study, we aimed to determine the prevalence and associated factors of enuresis in Saudi children in Hail, and to identify common methods used for its management. Subjects and Methods: A cross sectional epidemiological study performed among children living in Hail, Saudi Arabia. A selfadministered questionnaire was prepared for this study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the Taif region, the frequency of nocturnal enuresis was 7.81% [14] and 31.2% in a study in different regions of the kingdom [15]; in Riyadh, the prevalence of NE was 18.5%, with a higher burden among male children [16]. In Jazan, 76.4% of the children had NE [17], the prevalence of nocturnal enuresis in Hail was 22.7% [18], and it was 92.8% in Jeddah [21]. Compared to our findings, the prevalence of NE was 18% in Egypt [19] and 6.8% in Iran [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Taif region, the frequency of nocturnal enuresis was 7.81% [14] and 31.2% in a study in different regions of the kingdom [15]; in Riyadh, the prevalence of NE was 18.5%, with a higher burden among male children [16]. In Jazan, 76.4% of the children had NE [17], the prevalence of nocturnal enuresis in Hail was 22.7% [18], and it was 92.8% in Jeddah [21]. Compared to our findings, the prevalence of NE was 18% in Egypt [19] and 6.8% in Iran [26].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis showed that the type of delivery, history of anemia, mothers' education, and NE among the youngest children were significantly associated with perceived stress. A number of factors have been associated with NE, which include the child's age and gender, a family history of NE, pinworm infestation, lack of breastfeeding, poor academic performance, the level of parents' education, socioeconomic status, deep sleep, a history of urinary tract infections, a history of hospital admission after delivery, a history of diabetes, daytime enuresis, and tea and sweets consumption [14,15,[17][18][19][20][21]28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have evaluated the prevalence of NE in Saudi Arabia and have noted variations across different regions [ 13 17 ]. A recent study assessed the prevalence of NE in several cities in Saudi Arabia and found the prevalence to be 31.2% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%